A community based study of the incidence of dementia in subjects aged 85 years and over. Issue 5 (November 1995) - Gussekloo, J; Heeren, T J; Izaks, G J; Ligthart, G J; Rooijmans, H G
Abstract : The aim was to investigate the incidence rate of dementia for community residents aged 85 years and over. It was a two wave community study of 224 subjects (community residents including those residing in a nursing home) older than 85 years, restudied 4.1 years after a community prevalence study. A two stage method was used, comprising the mini mental state examination followed in a stratified sample by the geriatric mental state schedule (A3)/AGECAT. Incidence rates were based on person-years at risk. The overall incidence of dementia was 6.9 (95% confidence interval (95% CI) 4.8-9.1) per 100 person-years at risk. The incidence was significantly higher for women than for men; respectively 8.9 (95% CI 5.9-11.9) v 2.7 (95% CI 0.5-4.9) per 100 person-years at risk. In the fastest growing age group seven out of 100 persons develop dementia each year. Women, who constitute two thirds of the oldest old, seem to have a higher risk. Further research is needed into the risk factors for dementia in this age group.